Kajian Kurikulum Pendidikan Fisika dalam Membekali Kreativitas Mahasiswa Calon Guru Fisika (UPEJ Unnes Physics Education Journal, 2020)
Research aims to reveal design of Unnes Physics Education Curriculum related to development of student abilities who lead to creativity and learning in train student creativity who carried out based on the Unnes Physics Education Curriculum. The research method uses descriptive analysis with a quantitative-qualitative approach. The study used triangulation techniques. CPL and CPMK in the 2015 Physics Education Curriculum as samples of documentation method analysis related to train student creativity and interviews to students and distribution questionnaires to find out the level of students creativity. The results of the analysis show the Achievement of Graduate Learning (CPL) and Achievement of Course Learning (CPMK) of curriculum design has a very high creativity criteria with a percentage of 81%. These results are different from interviews result and research questionnaires which show that the implementation of the 2015 Physics Education Curriculum has not been maximized in equipping the creativity of physics education students at the highest level of creativity. It was stated that the results of the average percentage of questionnaires were 68% with high creativity criteria, and interviews were 52% with moderate creativity criteria. The results of the T-test obtained the Sig. (0.002) < 0.05 which indicates a significant difference between the level of student creativity in the field and the level of creativity in the 2015 Physics Education Curriculum design.